PENGARUH PERTUMBUHAN EKONOMI, EFISIENSI DAN LIKUIDITAS TERHADAP PROFITABILITAS PERBANKAN PADA BURSA EFEK INDONESIA - Niken Saraswati; Mulyono Mulyono (Ultima Accounting : Jurnal Ilmu Akuntansi, 2019)
A good bank must be efficient because efficiency will increase banking productivity and performance. As an institution that functions for banking intermediation, it must have a healthy financial condition to function properly and gain public trust. The purpose of this study is to examine the effect of Economic Growth, Efficiency and Liquidity on the profitability of banks in the Indonesia Stock Exchange. There are inconsistent research results from previous studies, regarding efficiency, liquidity and economic growth that can affect banking performance. The sample used in this study was 35 banks listed on the Indonesia Stock Exchange. Data processing in this study uses multiple regression with the help of SPSS version 20. The results of the study indicate that Economic Growth has a positive influence on bank profitability, for Efficiency and Liquidity has a negative effect on bank profitability. This research is expected to be useful both for the banking industry in making decisions and the government in making policies.